The expanding role of microRNAs in the biology and control of veterinary parasitic nematodes - Manikantan, Vishnu; Pires dos Santos, Andrea; Dangoudoubiyam, Sriveny (Frontiers in Veterinary Science, 2025)
Parasitic nematodes threaten animal health globally, contributing to substantial losses in livestock productivity and posing zoonotic risks through infections in companion animals. There is a growing concern over widespread resistance to anthelmintic drugs, necessitating new molecular approaches for parasite control. MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression and have emerged as key modulators of nematode development, growth, stage transitions, host-pathogen interactions, and parasite survival. Certain miRNAs are expressed in a stage- and sex-specific manner, and many are selectively secreted via extracellular vesicles, enabling direct interactions with the host. The detection of worm-derived miRNAs in blood of an infected host highlights their potential as early diagnostic biomarkers for nematode infections. Emerging evidence links miRNAs to anthelmintic resistance. This review provides an overview of miRNA biogenesis, gene regulation mechanisms, and current miRNA discovery and experimental validation approaches. Importantly, it highlights species-specific advances in miRNA research in parasitic nematode infections of veterinary importance, emphasizing their roles in parasite biology, immune modulation, and drug resistance.